O Museu José Antônio Pereira e as possibilidades de pesquisa histórica sobre a cidade de Campo Grande (MS) - Ayabe, Silvia (2024)
This research has as its guiding thread the investigation and analysis of the trajectory of the José Antônio Pereira Museum, a museum institution located in the city of Campo Grande, state of Mato Grosso do Sul. Since the beginning of the 1980s, the museum has selected, preserved and exposed a certain perspective on the emergence of the locality and the social and cultural implications of the arrival of squatters to the region, propagated by the memory of the family that lived there and, later, by their descendants and memoirist writings. With the title “The José Antônio Pereira Museum and the possibilities of historical research on the city of Campo Grande (MS)”, the objective of understanding contradictions that involve the museum narrative strongly linked to the official history of the city and academic studies is exposed. about the same and understand what are the possible versions of the city's history, starting from the museum narrative and relating history, education, heritage and museums.. The narratives presented here are based on the idea of concern for the preservation of local heritage, which presents a change in principles after the division of the former state of Mato Grosso. Therefore, I initially analyze Brazilian heritage processes in the historical field, then move on to issues of regional and local preservation. The heritage sites chosen in the city that was the focus of the study were described based on their official listing (municipal, state or federal), in order to contextualize the local dynamics and understand their priorities, given that the movement of memory is accompanied by that of forgetting. To introduce questions about the museum space, I presented as a theory the construction of memory through the uses of the past because museum spaces are arenas of disputes and thanks to their symbolic aspect, promoting memories, for this, I spoke with Nora (1993) , Le Goff (2003), Halbwachs (1990), Klas-Göran Karlsson (2011) and Hobsbawn (1998) and Chagas (2002). The results were obtained from the analysis of the historiographical production about the museum institution, the mass of documents that institutionalized the place, as well as theoretical-methodological reflections on the importance of a museum education that dialogues with academic discourses. The proposals, suggestions, adaptations made and presented here do not seek to put an end to a discussion, only to contribute to some concerns and present proposals that, by using the museum space as a source of information, strengthen the teaching process as a space for the construction of self based on respect for others.